2012
DOI: 10.1080/02687038.2012.693583
|View full text |Cite
|
Sign up to set email alerts
|

Long-term maintenance of novel vocabulary in persons with chronic aphasia

Abstract: Background:The study of novel word learning in aphasia can shed light on the functionality of patients' learning mechanisms and potentially help in treatment planning. Previous studies have indicated that persons with aphasia are able to learn some new vocabulary. However, these learning outcomes appear short-lived and evidence for the ability to use the newly learned words in the long term is lacking. Aims: Participants with aphasia and matched controls underwent short training where they were taught to name … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…An emerging body of research has employed the use of novel word learning to investigate verbal learning in adults with aphasia (Gupta et al, 2006;Tuomiranta et al, 2011;Tuomiranta et al, 2012). The use of unfamiliar pictures (i.e., novel semantics) paired with novel word forms in a novel word learning task is suggested to provide a relatively pure measure of individuals' verbal learning capacity.…”
Section: Influence Of Learning Ability On Aphasia Treatment Successmentioning
confidence: 99%
See 4 more Smart Citations
“…An emerging body of research has employed the use of novel word learning to investigate verbal learning in adults with aphasia (Gupta et al, 2006;Tuomiranta et al, 2011;Tuomiranta et al, 2012). The use of unfamiliar pictures (i.e., novel semantics) paired with novel word forms in a novel word learning task is suggested to provide a relatively pure measure of individuals' verbal learning capacity.…”
Section: Influence Of Learning Ability On Aphasia Treatment Successmentioning
confidence: 99%
“…A number of studies have explicitly evaluated verbal and non-verbal learning ability in adults with chronic aphasia (Gupta, Martin, Abbs, Schwart, & Lipinski, 2006;Kelly & Armstrong, 2009;Tuomiranta et al, 2011;Tuomiranta, Rautakoski, Rinne, Martin, & Laine, 2012;Vallila-Rohter & Kiran, 2013a, 2013b) and a detailed review of this research is provided in Chapter Five. This research has demonstrated that whilst individuals with aphasia are able to learn new information, both verbal and non-verbal learning mechanisms are impaired in adults with aphasia (Gupta et al, 2006;Kelly & Armstrong, 2009;Vallila-Rohter & Kiran, 2013a).…”
Section: Influence Of Learning Ability On Aphasia Treatment Successmentioning
confidence: 99%
See 3 more Smart Citations